2001
DOI: 10.1084/jem.194.4.379
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of Dendritic Cells Is Accompanied by Rapid Transcriptional Silencing of Class II Transactivator (Ciita) Expression

Abstract: Cell surface expression of major histocompatibility complex class II (MHCII) molecules is increased during the maturation of dendritic cells (DCs). This enhances their ability to present antigen and activate naive CD4+ T cells. In contrast to increased cell surface MHCII expression, de novo biosynthesis of MHCII mRNA is turned off during DC maturation. We show here that this is due to a remarkably rapid reduction in the synthesis of class II transactivator (CIITA) mRNA and protein. This reduction in CIITA expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
171
2
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 142 publications
(196 citation statements)
references
References 69 publications
(83 reference statements)
22
171
2
1
Order By: Relevance
“…Our data showing that the inhibitory phenotype is unique to CNS-DC while spleen DC from the same EAE animals are stimulatory (Fig. 2) and mature [15] are supported by the observation that spleen and LN DC from rats with EAE can transfer the disease to unprimed animals [28]. This indicates that this latter DC type used for the transfer is able to process and present autoantigens and to stimulate naive T cells [28].…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Our data showing that the inhibitory phenotype is unique to CNS-DC while spleen DC from the same EAE animals are stimulatory (Fig. 2) and mature [15] are supported by the observation that spleen and LN DC from rats with EAE can transfer the disease to unprimed animals [28]. This indicates that this latter DC type used for the transfer is able to process and present autoantigens and to stimulate naive T cells [28].…”
Section: Discussionsupporting
confidence: 70%
“…CIITA form I is indispensable for constitutive expression of MHC class II molecules in professional antigen-presenting cells (APC) such as DC and macrophages [5,12,14]. Its expression is high in immature DC and is then shut down after induction of maturation (reduction to 50% after X 1 h) [15]. Therefore, we hypothesized that the initiation of CNS autoimmunity was due to the invasion by immature DC.…”
Section: Dendritic Cells Having Intermediate Surface Mhc Class II Andmentioning
confidence: 99%
See 2 more Smart Citations
“…1B). Consistent with previous reports (Landmann et al, 2001), we observed a significant reduction in the level of DC-CIITA mRNA upon LPS-induction. Interestingly, the mRNA level of the DC-CASPIC did not change in the presence of LPS, indicating that the DC-CIITA-isoform was not regulated at transcriptional In silico mouse genome database search shows that the intron 1 of the mouse DC-CIITA gene contains exon-intron boundaries that agree with consensus splice donor, and thus divides intron 1 (white box) into three parts.…”
Section: Resultssupporting
confidence: 93%